Preparation process of a linaloe compound preparation for relieving pain of herpes zoster

CN122894447APending Publication Date: 2026-10-13BEIJING YIDETANG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611220417.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种缓解带状疱疹疼痛的沉香复合制剂制备工艺,解决了常规带状疱疹外用制剂受皮肤角质层阻滞,透皮吸收率低;且沉香提取物水溶性差易结晶,现有含油递送系统易发生液滴聚并与相分离,导致药物有效渗透通量下降,难以维持稳定的局部镇痛效果的问题

Benefits of technology

1、本发明通过L-薄荷醇与肉豆蔻酸异丙酯在受热条件下的分子间缔合形成低共熔体系,为沉香超临界提取物提供了适宜的溶解环境,减少脂溶性成分的析出与结晶,低共熔基质成分与皮肤角质层脂质相容性较好,在涂布给药时降低有效成分跨膜渗透的阻力,从而提升制剂中镇痛成分的透皮吸收效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122894447A_ABST
    Figure CN122894447A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of medical preparations, and discloses a preparation process of an eaglewood composite preparation for relieving herpes zoster pain, which comprises the following steps: heating L-mint alcohol and isopropyl myristate to form a low eutectic system, adding eaglewood supercritical extract to the low eutectic system to perform constant-temperature solubilization, adding polyoxyethylene 20 cetyl ether and hot phase initial water to perform heating, when an inflection point of sharp conductivity decrease is reached at 72-78 DEG C, heat preservation is performed, hot phase material is obtained, cold phase quenching water and sodium lactate aqueous solution are used to prepare a cold phase medium with a temperature of 8-15 DEG C, the hot phase material is continuously injected into the cold phase medium to perform quenching, stirring and balance are performed until room temperature, and then the material is discharged, so that the eaglewood extract solubility and transdermal absorption rate are improved by constructing a low eutectic system, the dispersed phase particle size is solidified by using phase transition temperature and quenching operation, and the liquid drop coalescence and phase separation are limited by combining with an electrostatic stability barrier, so that the physical stability of the preparation is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of pharmaceutical preparation technology, specifically to a preparation process for an agarwood compound preparation to relieve the pain of shingles. Background Technology

[0002] Herpes zoster is an acute infectious skin disease caused by the varicella-zoster virus. Patients often experience severe localized neuralgia distributed along the nerve pathway. To reduce the adverse reactions of systemic medication, topical application is a common way to relieve this type of neuralgia. Agarwood and its extracts contain various aromatic and sesquiterpenoid components, and are often explored clinically for analgesia and anti-inflammation.

[0003] However, in actual formulation development, the local delivery of agarwood extracts is limited by both physicochemical properties and physiological barriers. Agarwood extracts generally have low polarity and poor water solubility; when directly added to conventional aqueous gel or cream bases, the active ingredients easily precipitate and crystallize. Furthermore, the stratum corneum of human skin naturally blocks low-polarity drug components, making it difficult for conventional topical application methods to provide sufficient penetration drive, resulting in low transdermal absorption rates of the active ingredients.

[0004] To improve the solubility and penetration of these poorly soluble extracts, existing technologies often employ oil-based transdermal delivery systems. However, traditional emulsification processes rely heavily on simple mechanical shearing, resulting in thermodynamically unstable dispersed phase systems. During later storage or when exposed to temperature fluctuations, the oil droplets in the dispersed phase are prone to Oswald ripening, leading to droplet coalescence and even oil-water separation. This disruption of physical stability directly reduces the specific surface area of ​​the drug in contact with the skin, causing a decrease in drug penetration flux and making it impossible to maintain a stable and sustained local analgesic effect. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a preparation process for an agarwood compound formulation to relieve shingles pain. This process solves the problems of conventional topical shingles preparations being blocked by the stratum corneum of the skin, resulting in low transdermal absorption; and the poor water solubility and easy crystallization of agarwood extracts, which lead to droplet aggregation and phase separation in existing oil-containing delivery systems, resulting in a decrease in effective drug penetration and difficulty in maintaining a stable local analgesic effect.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a preparation process for an agarwood compound preparation to relieve shingles pain, using the following technical solution: A process for preparing an agarwood compound preparation to relieve shingles pain includes the following steps: Weigh the raw materials: 10-50 parts of supercritical agarwood extract, 30-80 parts of L-menthol, 80-150 parts of isopropyl myristate, 40-90 parts of polyoxyethylene 20 hexadecyl ether, 16.7-83.3 parts of sodium lactate aqueous solution with a mass fraction of 60wt%, and 546.7-823.3 parts of deionized water. Divide the deionized water into 124.5-146 parts of hot phase initial water and 401.7-698.8 parts of cold phase quenched water. L-menthol and isopropyl myristate were added sequentially to the hot phase reactor A, heated to a constant temperature and stirred. After the system melted and formed a homogeneous liquid, agarwood supercritical extract was added, and the mixture was stirred continuously at a constant temperature to solubilize the active ingredients. Next, add polyoxyethylene 20 cetyl ether and hot phase initial water, heat at the heating rate and monitor the conductivity in real time. When the temperature reaches 72-78℃ and the conductivity drops sharply, stop heating and keep the temperature constant. Reduce the stirring speed to maintain the temperature balance and obtain the hot phase material. Add cold phase quenching water and sodium lactate aqueous solution to cold phase reactor B, cool down and keep the bottom liquid temperature constant, start stirring to form a cold phase medium in a low temperature aqueous phase state; The hot phase material in the hot phase reactor A, which is in a heat preservation state, is continuously injected into the cold phase medium in the cold phase reactor B, and the conveying flow rate is controlled so that the transfer process is completed within a preset time. After the materials are transferred, stop cooling and continue stirring at low speed at room temperature. Stop stirring when the mixture naturally reaches room temperature, and discharge the material through the bottom valve to obtain the agarwood compound preparation.

[0007] By employing the above technical solutions, the synergistic effect of multiphase fluid dynamics and colloidal interface chemistry helps to improve the permeability and physical stability of composite formulations. The specific physicochemical processes are mainly reflected in the following aspects: In the formulation system, the hydroxyl group of the L-menthol molecule acts as a hydrogen bond donor, readily forming intermolecular associations with the carbonyl group of isopropyl myristate, which acts as a hydrogen bond acceptor. This hydrogen bond interaction alters the original spatial arrangement of the substances, forming a binary eutectic solvent with a lowered freezing point. This liquid eutectic system reduces the tendency for lipid-soluble components in the supercritical fluid extract of agarwood to crystallize, thus promoting the solubility of the active ingredients. Furthermore, the matrix exhibits good compatibility with the lipids of the stratum corneum, fluidizing the lipid bilayer structure to some extent and reducing the transmembrane resistance of the active ingredients.

[0008] During the controlled heating process, as the system temperature increases, water molecules around the polyoxyethylene segments of polyoxyethylene 20-hexadecyl ether gradually desorb, and the hydration degree of surfactant molecules decreases accordingly, causing a shift in the hydrophilic-lipophilic equilibrium of the system. When heated to the critical range of 72–78°C, the online-monitored conductivity shows a sharp downward trend, indicating that the continuous and dispersed phases of the system are reversing, transforming from a conductive aqueous continuous structure to an insulating oil continuous structure. In the region near this phase transition point, the surface tension at the oil-water interface is at a low level, and the dispersed phase can break into fine droplets under relatively small mechanical shear.

[0009] Subsequently, the high-temperature hot phase material, which is at the critical state of the aforementioned phase transition, is rapidly injected into the low-temperature cold phase medium, creating a large temperature gradient within the system. This causes the polyoxyethylene segments of the surfactant to rapidly rehydrate and expand, and the system subsequently transforms into an oil-in-water structure. The rapid cooling process under large temperature differences shortens the interfacial film recombination time to some extent, helping to solidify the particle size within a smaller range before frequent thermodynamic collisions occur in the dispersed phase droplets. This limits the kinetics of Oswald ripening and reduces the probability of droplet coalescence.

[0010] Furthermore, the sodium lactate pre-dissolved in the cold phase medium, after dissociation, tends to distribute near the oil-water interface of the nascent droplets, moderately increasing the thickness of the electrical double layer at the interface. Through the synergistic effect of steric hindrance and electrostatic repulsion, the physical anti-agglomeration properties of the droplets during storage are improved, while simultaneously making the osmotic pressure of the final formulation closer to the physiological environment of the human body.

[0011] Preferably, the component ratio of the raw materials, by weight, is as follows: 30 parts of supercritical agarwood extract, 50 parts of L-menthol, 100 parts of isopropyl myristate, 60 parts of polyoxyethylene 20 hexadecyl ether, 50 parts of sodium lactate aqueous solution with a mass fraction of 60 wt%, and 710 parts of deionized water. The deionized water consisted of 146 parts of hot initial water and 564 parts of cold quenched water.

[0012] By adopting the above technical solution, the limited material mass ratio ensures that L-menthol and isopropyl myristate are in a suitable ratio range, which helps to form a relatively stable hydrogen bond association state and provides a better drug loading space for agarwood extract; the corresponding oil-water ratio can also better match the aforementioned phase transformation process, which is conducive to obtaining a formulation product with a relatively concentrated particle size distribution.

[0013] Preferably, the supercritical fluid extract of agarwood is obtained by the following preparation method: Agarwood powder was loaded into a supercritical extraction vessel, high-purity carbon dioxide was used as the extraction fluid, the extraction pressure was controlled at 25-30 MPa, the extraction temperature was controlled at 40-50℃, and the dynamic extraction was carried out for 120-180 min. The supercritical fluid carrying the active ingredients then enters the separation vessel, where the desorption pressure is set to 5-8 MPa and the desorption temperature to 35-45°C to allow carbon dioxide to vaporize and separate. The extract is collected at the bottom of the separation vessel to obtain the supercritical extract of agarwood.

[0014] By adopting the above technical solution, the supercritical carbon dioxide fluid under the set parameters is conducive to the selective enrichment of medium and low polarity active ingredients such as agaric tetraol. The selected low extraction temperature reduces the pyrolysis loss of heat-sensitive aromatic components, and the extraction process does not require the participation of conventional organic solvents, which helps to improve the physicochemical purity of the final topical preparation.

[0015] Preferably, before loading the agarwood powder into the supercritical extraction vessel, a pretreatment step for the agarwood powder is also included: taking agarwood logs, mechanically crushing them, and passing them through a 40-60 mesh sieve to obtain agarwood powder.

[0016] By adopting the above technical solution, the logs are crushed to the above particle size range, which can moderately destroy the dense structure of lignin, providing a relatively sufficient contact area for subsequent fluid-solid mass transfer. At the same time, it can also prevent problems such as excessive pressure drop in the extraction material bed and local channeling caused by excessive powder refinement.

[0017] Preferably, during the process of solubilizing the active ingredient by constant temperature and continuous stirring, the heating temperature is set at 35-45°C, the stirring speed is controlled at 40-60 rpm, and the constant temperature and continuous stirring time is 20-40 min.

[0018] By adopting the above technical solution, this temperature range maintains a good flow state for the low-melting-point matrix while keeping it below the temperature at which the effective components of the extract are easily degraded by heat. Combined with a moderately low-velocity shear flow field, this facilitates the dispersion and dissolution of solid solutes in the liquid phase system.

[0019] Preferably, during the process of obtaining the hot phase material, the heating rate is 1.5 to 2.5 °C / min, the stirring speed is reduced to 20 to 40 rpm, and the holding time is 10 to 20 min.

[0020] By adopting the above technical solution, the set heating rate is relatively slow, which can reduce the risk of phase transition lag or signal delay caused by local overheating, and help online equipment to accurately capture the inflection point of phase interface reversal; the subsequent low-speed heat preservation process provides a certain buffer time for the directional adsorption and rearrangement of surfactant molecules at the oil-water interface.

[0021] Preferably, during the process of forming a cold phase medium in a low-temperature aqueous state, the temperature of the bottom liquid is cooled and kept constant at 8-15°C, and the stirring speed is controlled at 50-80 rpm.

[0022] By adopting the above technical solution, the preset low temperature environment can form a more obvious temperature difference between the two phases when the two phases are mixed, providing the required rapid cooling driving force. The set stirring speed can maintain the convective heat transfer inside the cold phase medium and reduce the formation of local temperature dead zones.

[0023] Preferably, during the process of continuously injecting the hot phase material in the hot phase reactor A, which is in a heat preservation state, into the cold phase medium in the cold phase reactor B, the continuous injection is carried out through a feed pipe extending below the liquid surface, and the preset time is 3 to 5 minutes.

[0024] By adopting the above technical solution, the feeding method below the liquid surface reduces air entrainment and subsequent foaming caused by material falling from a height, and controls the material transfer time within the above range. This not only meets the condition of rapid cooling and dispersion of hot phase materials, but also prevents the rapid fluctuation of cold phase reactor temperature caused by excessive single injection flow.

[0025] Preferably, in the step after the material transfer is completed, the stirring speed is maintained at 30-50 rpm for 10-20 minutes, and the mixture is allowed to naturally equilibrate to room temperature, specifically to 20-30°C.

[0026] By adopting the above technical solution, the gentle stirring process at the end of the preparation helps to slowly release the residual temperature difference and concentration difference in the system, which to some extent alleviates the internal stress left by the drastic temperature drop operation and promotes the mixed system to gradually tend to a more stable colloidal dispersion state.

[0027] Preferably, the appearance of the agarwood compound preparation is translucent to milky white with a bluish tint.

[0028] By adopting the above technical solution, the bluish light phenomenon exhibited by the system is usually attributed to the Tyndall scattering effect, which indicates that a small-scale and relatively uniformly distributed micro-dispersed phase structure has been formed inside the formulation, and its particle size range is consistent with specific optical scattering conditions.

[0029] This invention provides a preparation process for an agarwood compound formulation that relieves pain from shingles. It has the following beneficial effects: 1. This invention utilizes the intermolecular association between L-menthol and isopropyl myristate under heating conditions to form a eutectic system, providing a suitable dissolution environment for the supercritical extract of agarwood, reducing the precipitation and crystallization of lipid-soluble components, and the eutectic matrix components have good compatibility with the lipids of the stratum corneum of the skin, reducing the resistance to transmembrane permeation of active ingredients when applied topically, thereby improving the transdermal absorption efficiency of analgesic components in the formulation.

[0030] 2. This invention utilizes the phase transition characteristics of polyoxyethylene 20-hexadecyl ether in the 72-78°C range, combined with a rapid cooling operation that directly injects the hot phase material into a cold phase medium at 8-15°C, allowing the surfactant to quickly rehydrate and solidify its particle size before thermodynamic collisions occur in the dispersed phase droplets. Combined with the electrostatic repulsion provided by the dissociation of sodium lactate in the cold phase medium, this effectively limits droplet aggregation and growth, improving the formulation system's ability to prevent phase separation and its long-term storage stability.

[0031] 3. This invention uses supercritical carbon dioxide fluid technology to extract agarwood raw materials. The relatively low extraction temperature reduces the loss of heat-sensitive aromatic analgesic components, and no conventional organic solvents are involved in the entire process, ensuring the physicochemical purity of the topical preparation. By combining real-time conductivity monitoring in the preparation process, the critical temperature inflection point of phase interface reversal of the system can be captured, providing a quantitative control index for phase transformation operation and improving the process reproducibility of batch preparation. Attached Figure Description

[0032] Figure 1 The differential scanning calorimetry and infrared spectra of each test object of the present invention are shown, wherein (a) is a differential scanning calorimetry curve and (b) is a Fourier transform infrared full spectrum. Figure 2 This is a continuous tracking curve of phase transition temperature and conductivity of the present invention; Figure 3 This is a high-performance liquid chromatogram of the target components of the agarwood extract of the present invention; Figure 4 The diagram shows the dynamic light scattering particle size distribution curve of the present invention, wherein (a) is the initial particle size distribution curve of the sample, and (b) is the particle size distribution curve of the sample after undergoing accelerated aging treatment. Figure 5 This is a graph showing the in vitro cumulative permeation kinetics of the present invention. Detailed Implementation

[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] In the following specific embodiments, "parts" refers to parts by weight. In the following examples and comparative operations, the weight ratio of each raw material is expressed in grams as the actual unit of mass measurement, that is, 1 part corresponds to 1 gram of material mass.

[0035] Preparation Example 1: This preparation example provides a method for preparing agarwood supercritical extract, including the following steps: 1000g of agarwood logs were mechanically crushed and passed through a 50-mesh sieve to obtain agarwood powder. The agarwood powder was then placed in a supercritical extraction vessel, and high-purity carbon dioxide was used as the extraction fluid. The extraction pressure was controlled at 28MPa, the extraction temperature at 45℃, and dynamic extraction was performed for 150min. The supercritical fluid carrying the effective components then entered a separation vessel, where the desorption pressure was set at 6MPa and the desorption temperature at 40℃ to allow the carbon dioxide to vaporize and separate. The extract was collected at the bottom of the separation vessel to obtain the agarwood supercritical extract.

[0036] Preparation Example 2: This preparation example provides a method for preparing agarwood supercritical extract, including the following steps: 1000g of agarwood logs were mechanically crushed and passed through a 40-mesh sieve to obtain agarwood powder. The agarwood powder was then placed in a supercritical extraction vessel, and high-purity carbon dioxide was used as the extraction fluid. The extraction pressure was controlled at 25MPa, the extraction temperature at 40℃, and dynamic extraction was performed for 120min. The supercritical fluid carrying the effective components then entered a separation vessel, where the desorption pressure was set at 5MPa and the desorption temperature at 35℃ to allow the carbon dioxide to vaporize and separate. The extract was collected at the bottom of the separation vessel to obtain the agarwood supercritical extract.

[0037] Preparation Example 3: This preparation example provides a method for preparing agarwood supercritical extract, including the following steps: 1000g of agarwood logs were mechanically crushed and passed through a 60-mesh sieve to obtain agarwood powder. The agarwood powder was then placed in a supercritical extraction vessel, and high-purity carbon dioxide was used as the extraction fluid. The extraction pressure was controlled at 30MPa, the extraction temperature at 50℃, and dynamic extraction was performed for 180min. The supercritical fluid carrying the effective components then entered a separation vessel, where the desorption pressure was set at 8MPa and the desorption temperature at 45℃ to allow the carbon dioxide to vaporize and separate. The extract was collected at the bottom of the separation vessel to obtain the agarwood supercritical extract.

[0038] Example 1:

[0039] This embodiment provides a process for preparing an agarwood compound preparation to relieve shingles pain, including the following steps: S1, weigh 30g of the supercritical extract of agarwood obtained in Preparation Example 1, 50g of L-menthol, 100g of isopropyl myristate, 60g of polyoxyethylene (20) hexadecyl ether, 50g of sodium lactate aqueous solution with a mass fraction of 60wt%, and 710g of deionized water, and divide them into 146g of hot phase initial water and 564g of cold phase quenched water.

[0040] S2, turn on the jacket temperature control system of the hot phase reactor A, set the water bath temperature to 40℃, add L-menthol and isopropyl myristate in sequence, turn on the stirring speed to 50 rpm, and after the system melts to form a transparent and homogeneous liquid, add the agarwood supercritical extract, and stir continuously at a constant temperature for 30 min to completely solubilize the active ingredients. Add polyoxyethylene (20) hexadecyl ether and 146g of hot phase initial water to the hot phase reactor A, and heat at a heating rate of 2.0℃ / min. Use an online conductivity meter to monitor the conductivity in real time. When the system temperature reaches 75℃ and the conductivity shows a sharp drop, stop heating and keep the temperature constant at 75±1℃. Reduce the stirring speed to 30 rpm and keep the temperature balanced for 15 min.

[0041] S3. While the S2 heat preservation process is in progress, 564g of cold phase quenching water and 50g of 60wt% sodium lactate aqueous solution are added to the cold phase reactor B. The jacketed refrigeration system is turned on to lower the bottom liquid temperature to 12℃ and keep it constant. The stirring speed is turned on to 60rpm to form a cold phase medium in a low temperature aqueous phase state.

[0042] S4. Turn on the transfer pump connecting reactor A and reactor B. The hot phase material in reactor A, which is kept at 75°C, is continuously injected into the cold phase medium in reactor B through the feed pipe that extends below the liquid surface. Control the transfer flow rate so that the transfer process is completed within 4 minutes.

[0043] S5. After the material transfer is completed, close the jacketed refrigerant channel of reactor B and continue to stir at a low speed of 40 rpm for 15 minutes at room temperature. Stop stirring when the mixing system in reactor B naturally reaches 25°C. Discharge the material through the bottom valve to obtain a translucent to milky white agarwood compound preparation with a bluish tint.

[0044] Example 2:

[0045] This embodiment provides a process for preparing an agarwood compound preparation to relieve shingles pain, including the following steps: S1, weigh 10g of the supercritical extract of agarwood obtained in Preparation Example 2, 30g of L-menthol, 80g of isopropyl myristate, 40g of polyoxyethylene (20) hexadecyl ether, 16.7g of sodium lactate aqueous solution with a mass fraction of 60wt%, and 823.3g of deionized water, and divide them into 124.5g of hot phase initial water and 698.8g of cold phase quenched water.

[0046] S2, turn on the jacket temperature control system of the hot phase reactor A, set the water bath temperature to 35℃, add L-menthol and isopropyl myristate in sequence, turn on the stirring speed to 40 rpm, after the system melts and forms a transparent and homogeneous liquid, add the agarwood supercritical extract, and stir continuously at a constant temperature for 20 min to completely solubilize the active ingredients. Add polyoxyethylene (20) hexadecyl ether and 124.5 g of hot phase initial water to hot phase reactor A, heat at a heating rate of 1.5℃ / min, monitor the conductivity in real time using an online conductivity meter, when the system temperature reaches 72℃ and the conductivity shows a sharp drop in inflection point, stop heating and keep the temperature constant at 72±1℃, reduce the stirring speed to 20 rpm, and keep the temperature balanced for 10 min.

[0047] S3. While the S2 heat preservation process is in progress, 698.8g of cold phase quenching water and 16.7g of 60wt% sodium lactate aqueous solution are added to the cold phase reactor B. The jacketed refrigeration system is turned on to lower the bottom liquid temperature to 10℃ and keep it constant. The stirring speed is turned on to 50rpm to form a cold phase medium in a low temperature aqueous phase state.

[0048] S4. Turn on the transfer pump connecting reactor A and reactor B. The hot phase material in reactor A, which is kept at 72°C, is continuously injected into the cold phase medium in reactor B through the feed pipe that extends below the liquid surface. Control the transfer flow rate so that the transfer process is completed within 3 minutes.

[0049] S5. After the material transfer is completed, close the jacketed refrigerant channel of reactor B and continue to stir at a low speed of 30 rpm for 10 minutes at room temperature. Stop stirring when the mixing system in reactor B naturally reaches 20°C. Discharge the material through the bottom valve to obtain a translucent to milky white agarwood compound preparation with a bluish tint.

[0050] Example 3:

[0051] This embodiment provides a process for preparing an agarwood compound preparation to relieve shingles pain, including the following steps: S1, weigh 50g of the supercritical agarwood extract obtained in Preparation Example 3, 80g of L-menthol, 150g of isopropyl myristate, 90g of polyoxyethylene (20) hexadecyl ether, 83.3g of sodium lactate aqueous solution with a mass fraction of 60wt%, and 546.7g of deionized water, and divide them into 145g of hot phase initial water and 401.7g of cold phase quenched water.

[0052] S2, turn on the jacket temperature control system of the hot phase reactor A, set the water bath temperature to 45℃, add L-menthol and isopropyl myristate in sequence, turn on the stirring speed to 60 rpm, after the system melts and forms a transparent and homogeneous liquid, add agarwood supercritical extract, and stir continuously at constant temperature for 40 min to completely solubilize the active ingredients. Add polyoxyethylene (20) hexadecyl ether and 145g of hot phase initial water to hot phase reactor A, heat at a heating rate of 2.5℃ / min, monitor the conductivity in real time using an online conductivity meter, when the system temperature reaches 78℃ and the conductivity shows a sharp drop in inflection point, stop heating and keep the temperature constant at 78±1℃, reduce the stirring speed to 40 rpm, and keep the temperature balanced for 20 min.

[0053] S3. While the S2 heat preservation process is in progress, 401.7g of cold phase quenching water and 83.3g of 60wt% sodium lactate aqueous solution are added to the cold phase reactor B. The jacketed refrigeration system is turned on to lower the bottom liquid temperature to 15℃ and keep it constant. The stirring speed is turned on to 80rpm to form a cold phase medium in a low temperature aqueous phase state.

[0054] S4. Turn on the transfer pump connecting reactor A and reactor B. The hot phase material in reactor A, which is kept at 78°C, is continuously injected into the cold phase medium in reactor B through the feed pipe that extends below the liquid surface. Control the transfer flow rate so that the transfer process is completed within 5 minutes.

[0055] S5. After the material transfer is completed, close the jacketed refrigerant channel of reactor B and continue to stir at a low speed of 50 rpm for 20 minutes at room temperature. Stop stirring when the mixing system in reactor B naturally reaches 30°C. Discharge the material through the bottom valve to obtain a translucent to milky white agarwood compound preparation with a bluish tint.

[0056] Example 4:

[0057] This embodiment provides a process for preparing an agarwood compound preparation to relieve shingles pain, including the following steps: S1, weigh 20g of the supercritical agarwood extract obtained in Preparation Example 1, 40g of L-menthol, 120g of isopropyl myristate, 50g of polyoxyethylene (20) hexadecyl ether, 33.3g of sodium lactate aqueous solution with a mass fraction of 60wt%, and 736.7g of deionized water, and divide them into 140g of hot phase initial water and 596.7g of cold phase quenched water.

[0058] S2, turn on the jacket temperature control system of the hot phase reactor A, set the water bath temperature to 40℃, add L-menthol and isopropyl myristate in sequence, turn on the stirring speed to 50 rpm, and after the system melts to form a transparent and homogeneous liquid, add the agarwood supercritical extract, and stir continuously at a constant temperature for 30 min to completely solubilize the active ingredients. Add polyoxyethylene (20) hexadecyl ether and 140g of hot phase initial water to the hot phase reactor A, and heat at a heating rate of 2.0℃ / min. Use an online conductivity meter to monitor the conductivity in real time. When the system temperature reaches 74℃ and the conductivity shows a sharp drop, stop heating and keep the temperature constant at 74±1℃. Reduce the stirring speed to 30 rpm and keep the temperature balanced for 15 min.

[0059] S3. While the S2 heat preservation process is in progress, 596.7g of cold phase quenching water and 33.3g of 60wt% sodium lactate aqueous solution are added to the cold phase reactor B. The jacketed refrigeration system is turned on to lower the bottom liquid temperature to 8℃ and keep it constant. The stirring speed is turned on to 60rpm to form a cold phase medium in a low temperature aqueous phase state.

[0060] S4. Turn on the transfer pump connecting reactor A and reactor B. The hot phase material in reactor A, which is kept at 74°C, is continuously injected into the cold phase medium in reactor B through the feed pipe that extends below the liquid surface. Control the transfer flow rate so that the transfer process is completed within 3 minutes.

[0061] S5. After the material transfer is completed, close the jacketed refrigerant channel of reactor B and continue to stir at a low speed of 40 rpm for 15 minutes at room temperature. Stop stirring when the mixing system in reactor B naturally reaches 22°C. Discharge the material through the bottom valve to obtain a translucent to milky white agarwood compound preparation with a bluish tint.

[0062] Comparative Example 1: Compared with Example 1, the difference is that: instead of using a spontaneous emulsification process based on phase transition temperature, all raw materials were mixed and then homogenized and emulsified at 5000 rpm for 30 minutes using a conventional high-speed shear homogenizer, and the phase transition point was not controlled throughout the process, while the rest were the same.

[0063] Comparative Example 2: Compared with Example 1, the difference is that the dual-reactor dynamic mixing rapid temperature drop process is not used. Instead, a single-reactor cooling method is used. That is, after the temperature in the hot phase reactor A is raised to 75°C and kept at equilibrium, chilled water is directly introduced through the jacket to slowly cool down to room temperature. The water and sodium lactate in the original cold phase medium are added to the hot phase reactor A in one step S2. The rest are the same.

[0064] Comparative Example 3: Compared with Example 1, the difference is that sodium lactate aqueous solution was not added to the formula, but was replaced by an equal mass of deionized water, and the cold phase medium in step S3 was simply deionized water, while the rest were the same.

[0065] Comparative Example 4: Compared with Example 1, the difference is that the order of adding electrolytes was changed. In step S2, 60 wt% sodium lactate aqueous solution was directly added to the hot phase reactor A. In step S3, only deionized water was retained as the cold phase medium. All other steps are the same.

[0066] Comparative Example 5: Compared with Example 1, the difference is that L-menthol was not added to the formulation, but was replaced by an equal mass of isopropyl myristate, that is, the total amount of isopropyl myristate was 150g, and a eutectic solvent system was not constructed, but everything else was the same.

[0067] Test Example 1: L-menthol monomer reference standard and isopropyl myristate monomer reference standard were taken as comparative test samples respectively; according to the process and ratio of step S2 in Example 1, L-menthol and isopropyl myristate were mixed and heated in a water bath to melt, and the transparent liquid before the addition of agarwood supercritical extract was taken as the binary matrix test sample.

[0068] Thermodynamic analysis of the three samples was performed using differential scanning calorimetry (DSC). Samples ranging from 4.5 to 6.5 mg were weighed and placed in standard aluminum crucibles, which were then pressed and sealed. An empty aluminum crucible was used as a reference. The test temperature range was set from -50 to 80 °C, with heating and cooling rates controlled at 10 °C / min. High-purity nitrogen was used as the purge gas during the test, with a flow rate of 50 mL / min. The heat flux versus temperature curves for each sample were recorded.

[0069] Fourier transform infrared spectroscopy was used to analyze the structure of the three samples. The L-menthol monomer sample was pretreated using the potassium bromide pellet method; the isopropyl myristate monomer sample and the binary matrix test sample were directly coated onto the surface of a potassium bromide window using the liquid film method. The instrument scanning range was set to 4000 cm⁻¹. -1 ~400cm -1 The resolution is set to 4cm. -1 The number of scans for both the background signal and the sample was set to 32. The test was conducted at room temperature, and the infrared transmission spectra of each sample were recorded.

[0070] Table 1. Differential Scanning Calorimetry and Infrared Spectroscopy Test Data

[0071] in conclusion: According to Table 1 and Figure 1 The test results showed that, in differential scanning calorimetry (DSC), the characteristic endothermic peak of L-menthol monomer appeared around 42.68℃, while the endothermic peak of isopropyl myristate appeared around 5.34℃. The binary matrix sample formed by the mixture of the two showed a significant shift of its endothermic peak towards the low-temperature region, with the peak value dropping to -14.82℃, accompanied by a broadening of the endothermic peak shape. This reflects the melting point suppression effect of the mixed system relative to the single component.

[0072] In infrared spectroscopy, the L-menthol monomer was measured at 3241.5 cm⁻¹. -1 The peak exhibits a characteristic hydroxyl stretching vibration at 3412.7 cm⁻¹, while isopropyl myristate shows no related absorption in this region; however, in the binary matrix sample, this hydroxyl characteristic peak shifts to 3412.7 cm⁻¹. -1 The low-temperature shift of the endothermic peak and the frequency shift of the infrared characteristic absorption peak mentioned above indicate that hydrogen bonding has occurred between L-menthol and isopropyl myristate molecules in the mixed system.

[0073] Intermolecular interactions help alter the spatial arrangement of the original single crystal, forming a eutectic system that exhibits a homogeneous liquid state at room temperature. This data trend provides physicochemical data support for the formation mechanism of the agarwood extract solubilizing carrier described in this invention, as well as for the subsequent transdermal mechanism based on improved lipid fluidity.

[0074] Test Example 2: The hot phase materials in the heating stage of step S2 in Examples 1 to 4 were selected as test samples.

[0075] Dynamic monitoring was performed using an online conductivity meter. In step S2 of each embodiment, after adding polyoxyethylene (20) hexadecyl ether and hot phase initial water and starting the heating program, the detection electrode of the conductivity meter was placed below the liquid surface in the hot phase container to maintain continuous measurement.

[0076] The monitoring temperature range was set to 50℃~85℃, and the instrument performed continuous sampling. Dynamic flow data of material conductivity as a function of temperature were collected during the heating process, and the temperature range corresponding to when the conductivity showed a significant decreasing trend was observed.

[0077] Table 2. Record of system conductivity at specific discrete temperatures during the heating process.

[0078] in conclusion: According to Table 2 and Figure 2The test data show that in the initial stage of heating in Examples 1 to 4, the conductivity of the system increased accordingly with the increase of temperature. When the temperature reached the vicinity of 75℃, 72℃, 78℃ and 74℃ respectively, the conductivity curves of each group of systems showed a downward inflection point, and then the values ​​remained in a lower range.

[0079] The nonlinear variation in conductivity indicates a change in the continuous phase state within the system. In the lower temperature range, the hydrophilic portion of nonionic surfactant molecules hydrates with water molecules, and the aqueous phase, as the continuous phase, is beneficial for maintaining the conductive network. As the temperature increases, surfactant molecules undergo dehydration, and their hydrophilic-lipophilic equilibrium adjusts accordingly. When entering a specific temperature range, the system transitions to a structural state where the oil phase is the continuous phase, thereby hindering the original conductive pathways.

[0080] The test results provide a physicochemical reference for the heat preservation temperature parameters set in step S2 of each embodiment, indicating that the selected temperature range is in the critical region of phase transformation of the system, which helps to change the surface tension conditions of the interface and provides a preliminary foundation for the formation of the dispersion system in subsequent processes.

[0081] Test Example 3: The agarwood compound preparations prepared in Examples 1 to 4 and the agarwood compound preparation prepared in Comparative Example 1 were used as test samples, while the agarwood supercritical extract obtained in Preparation Example 1 was used as a control sample.

[0082] Weigh out samples of each of the above-mentioned preparations containing equal masses of agarwood supercritical extract, place them in a suitable container, add chromatographically pure methanol, and sonicate at room temperature for 30 min. Transfer the extract and dilute to 10 mL, centrifuge at 12000 rpm for 10 min, collect the supernatant and filter through a 0.22 μm microporous membrane, and collect the filtrate as the test solution. Separately weigh out 10.0 mg of agarwood supercritical extract, dissolve it in methanol and dilute to 10 mL, filter through a conventional microporous membrane, and use as the reference solution.

[0083] The analysis was performed using high-performance liquid chromatography (HPLC). Chromatographic conditions included: an octadecylsilane-bonded silica column; a gradient elution system of acetonitrile and 0.1% formic acid aqueous solution as the mobile phase; a detection wavelength of 252 nm; a flow rate of 1.0 mL / min; a column temperature of 30 °C; and an injection volume of 10 μL. Chromatograms were recorded from 0 to 30 min. Peak area data of the target characteristic peaks were extracted, and the retention rate of the target component in the formulation was calculated as: retention rate = actual peak area of ​​the test sample / peak area of ​​the theoretical reference solution × 100%.

[0084] Table 3. Test data on the retention rate of target active ingredients in agarwood compound preparations.

[0085] in conclusion: According to Table 3 and Figure 3 The test data, under the set chromatographic analysis conditions, showed that the target characteristic peak was detected in the reference solution at a retention time of approximately 16.5 min. The retention rate of the target component in the test solutions of each embodiment was within the range of 93.69% to 96.78%; the retention rate of the component in the test solution of Comparative Example 1 was measured to be 68.51%, and the chromatogram showed additional absorption signals in the retention time region close to the target peak.

[0086] The data distribution indicates that Comparative Example 1, which employs a continuous high-frequency mechanical shearing process, had a certain physical impact on the extract system during use, manifested as a decrease in the chromatographic peak area of ​​some target components. In contrast, the rapid thermal cooling phase transition process used in this embodiment can be carried out under lower mechanical force conditions. This test result provides preliminary physicochemical data validation for the process design of protecting heat-sensitive or force-sensitive components in this scheme.

[0087] Test Example 4: The agarwood compound preparations prepared in Examples 1 to 4 and Comparative Examples 2 to 4 were used as test samples.

[0088] Each group of samples was placed into separate glass vials and sealed. The samples were then subjected to freeze-thaw cycles in a constant temperature device. The conditions for each cycle were set as follows: freezing at -20℃ for 24 hours, followed by transfer to a 40℃ incubator for 24 hours. After completing three cycles, the samples were removed and equilibrated at 25℃, and their macroscopic appearance was recorded.

[0089] The particle size parameters of the samples were determined using a dynamic light scattering instrument. Initial samples without freeze-thaw treatment and test samples after aging treatment were appropriately diluted with deionized water to adjust the transmittance. The test temperature was set at 25℃ and the scattering angle at 173°. The Z-mean particle size and polydispersity index of the system were recorded. Each sample was measured in triplicate, and the average value was taken.

[0090] Table 4. Test data of particle size and polydispersity index of compound formulation before and after accelerated treatment.

[0091] in conclusion: According to Table 4 and Figure 4According to the test data, the average particle size of Examples 1 to 4 was between 109.8 and 132.3 nm in the initial stage of preparation, and the polydispersity index was relatively low. After repeated freeze-thaw cycles, the average particle size and polydispersity index of the above samples did not increase, and the appearance remained uniform. Comparative Example 2, which used a single-reactor cooling process, had an initial average particle size of 251.6 nm. After aging, the average particle size increased to 623.4 nm, and the spectrum showed that its distribution range was significantly broadened. Comparative Example 3, which did not add sodium lactate, had a relatively small initial particle size, but after aging, the particle size distribution showed a trend of migrating to the larger particle size range. The spectrum showed secondary aggregation peaks, and macroscopic phase separation occurred. Comparative Example 4, which adjusted the electrolyte addition sequence, had higher initial and post-aging particle size parameters.

[0092] Test results indicate that the fluid dynamic transfer and cooling control method employed in this scheme helps to shorten the droplet stabilization time in the phase transition critical region and reduces the probability of thermodynamic collisions during natural cooling. Simultaneously, the sodium lactate component added under specific process timings exerts certain physicochemical effects at the oil-water interface. This test data provides an experimental reference for evaluating the physical stability of the formulation system under alternating temperature environments.

[0093] Test Example 5: The agarwood compound preparations prepared in Examples 1 to 4, Comparative Example 1 and Comparative Example 5 were used as test samples.

[0094] Ex vivo hairless mouse back skin treated with physiological saline was selected as a barrier material and fixed between the supply and receiving cells of the Franz diffusion cell. The orientation of the skin was adjusted so that the stratum corneum side faced the supply cell.

[0095] Add a 30% ethanol-saline mixture to the receiving pool as the receiving solution to remove air bubbles from the device. Maintain the temperature of the receiving pool at 32°C by turning on the water bath circulation and keeping the device magnetically stirred. Add equal masses of each group of test samples to the skin surface in the supply pool.

[0096] Sampling time points were set at 1h, 2h, 4h, 6h, 8h, 12h, and 24h. At the corresponding time point, 1.0mL of liquid was drawn from the sampling port of the receiving cell, and 1.0mL of fresh receiving liquid at the same temperature was immediately added to the receiving cell after sampling.

[0097] The obtained liquid was filtered through a microporous membrane, and the concentration of linalool in the filtrate was determined by high performance liquid chromatography. The cumulative permeation per unit area was recorded and calculated.

[0098] Table 5. Cumulative permeation data of target components in each group of samples at different time points (μg / cm³) 2 )

[0099] in conclusion: According to Table 5 and Figure 5 According to the test data, in Examples 1 to 4, the cumulative permeation of the target component was in a relatively high range within the set test period. The steady-state permeation linear region showed that the permeation curve of the example group had a large constant slope in this stage, indicating that the system could maintain a relatively high and stable continuous permeation rate after wetting the barrier.

[0100] Comparative Example 1, prepared using a conventional mechanical homogenization process, showed lower cumulative penetration values ​​at each time point compared to the Example Group. Comparative Example 5, whose formulation removed L-menthol, failed to construct a eutectic system with isopropyl myristate, resulting in lower cumulative penetration values ​​for its target component.

[0101] The test results indicate that the specific combination of excipients had a certain physicochemical impact on the process of extract components penetrating the in vitro model. At the same time, the smaller particle size of the dispersed phase formed under the specific process increased the contact area between the droplets and the barrier surface to a certain extent, providing a reference for evaluating the in vitro drug delivery behavior of the compound formulation of this scheme.

Claims

1. A preparation process for an agarwood compound preparation for relieving shingles pain, characterized in that, Includes the following steps: Weigh the raw materials: 10-50 parts of supercritical agarwood extract, 30-80 parts of L-menthol, 80-150 parts of isopropyl myristate, 40-90 parts of polyoxyethylene (20) hexadecyl ether, 16.7-83.3 parts of sodium lactate aqueous solution with a mass fraction of 60wt%, and 546.7-823.3 parts of deionized water. Divide the deionized water into 124.5-146 parts of hot phase initial water and 401.7-698.8 parts of cold phase quenched water. L-menthol and isopropyl myristate were added sequentially to a hot phase reactor A, heated to a constant temperature and stirred. After the system melted and formed a homogeneous liquid, the agarwood supercritical extract was added, and the mixture was stirred continuously at a constant temperature to solubilize the active ingredients. Next, the polyoxyethylene (20) hexadecyl ether and the hot phase initial water are added, and the heating is carried out at the heating rate while the conductivity is monitored in real time. When the temperature reaches 72-78°C and the conductivity drops sharply, the heating is stopped and the temperature is kept constant. The stirring speed is reduced to maintain the temperature balance and the hot phase material is obtained. Add the cold phase quenching water and the sodium lactate aqueous solution to the cold phase reactor B, cool down and keep the bottom liquid temperature constant, start stirring to form a cold phase medium in a low temperature aqueous phase state; The hot phase material in the hot phase reactor A, which is in a heat preservation state, is continuously injected into the cold phase medium in the cold phase reactor B, and the conveying flow rate is controlled so that the transfer process is completed within a preset time. After the materials are transferred, stop cooling and continue stirring at low speed at room temperature. Stop stirring when the mixture naturally reaches room temperature, and discharge the material through the bottom valve to obtain the agarwood compound preparation.

2. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, The composition ratio of the raw materials, by weight, is as follows: 30 parts of supercritical agarwood extract, 50 parts of L-menthol, 100 parts of isopropyl myristate, 60 parts of polyoxyethylene (20) hexadecyl ether, 50 parts of sodium lactate aqueous solution with a mass fraction of 60wt%, and 710 parts of deionized water. The deionized water consists of 146 parts of hot initial water and 564 parts of cold quenched water.

3. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, The supercritical extract of agarwood was obtained by the following preparation method: Agarwood powder was loaded into a supercritical extraction vessel, high-purity carbon dioxide was used as the extraction fluid, the extraction pressure was controlled at 25-30 MPa, the extraction temperature was controlled at 40-50℃, and the dynamic extraction was carried out for 120-180 min. The supercritical fluid carrying the active ingredients then enters the separation vessel, where the desorption pressure is set to 5-8 MPa and the desorption temperature to 35-45°C to allow carbon dioxide to vaporize and separate. The extract is collected at the bottom of the separation vessel to obtain the supercritical extract of agarwood.

4. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 3, characterized in that, Before the agarwood powder is loaded into the supercritical extraction vessel, a pretreatment step for the agarwood powder is also included: Agarwood logs are mechanically crushed and then passed through a 40-60 mesh sieve to obtain agarwood powder.

5. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, During the process of solubilizing the active ingredients by constant temperature and continuous stirring, the heating and constant temperature is set at a water bath temperature of 35-45°C, the stirring speed is controlled at 40-60 rpm, and the constant temperature and continuous stirring time is 20-40 min.

6. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, During the process of obtaining the hot phase material, the heating rate is 1.5 to 2.5 °C / min, the stirring speed is reduced to 20 to 40 rpm, and the heat preservation and equilibrium time is 10 to 20 min.

7. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, During the process of forming a cold phase medium in a low-temperature aqueous state, the cooling and stabilizing of the bottom liquid temperature is to reduce the temperature to and stabilize it at 8-15°C, and the stirring speed is controlled at 50-80 rpm.

8. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, During the process of continuously injecting the hot phase material in the hot phase reactor A, which is in a heat preservation state, into the cold phase medium in the cold phase reactor B, the continuous injection is carried out through a feed pipe extending below the liquid surface, and the preset time is 3 to 5 minutes.

9. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, In the step after the material transfer is completed, the speed of maintaining low-speed stirring is controlled at 30-50 rpm for 10-20 minutes, and the natural equilibrium to room temperature is specifically equilibrium to 20-30°C.

10. The preparation process of an agarwood compound preparation for relieving shingles pain according to claim 1, characterized in that, The appearance of the agarwood compound preparation is translucent to milky white with a bluish tint.